The molecular signaling of exercise and obesity in the microbiota-gut-brain axis - Ribeiro, Filipe M.; Silva, Maycon A.; Lyssa, Victória; Marques, Gabriel; Lima, Henny K.; Franco, Octavio L.; Petriz, Bernardo (Frontiers in Endocrinology, 2022)
Obesity is one of the major pandemics of the 21st century. Due to its multifactorial etiology, its treatment requires several actions, including dietary intervention and physical exercise. Excessive fat accumulation leads to several health problems involving alteration in the gut-microbiota-brain axis. This axis is characterized by multiple biological systems generating a network that allows bidirectional communication between intestinal bacteria and brain. This mutual communication maintains the homeostasis of the gastrointestinal, central nervous and microbial systems of animals. Moreover, this axis involves inflammatory, neural, and endocrine mechanisms, contributes to obesity pathogenesis. The axis also acts in appetite and satiety control and synthesizing hormones that participate in gastrointestinal functions. Exercise is a nonpharmacologic agent commonly used to prevent and treat obesity and other chronic degenerative diseases. Besides increasing energy expenditure, exercise induces the synthesis and liberation of several muscle-derived myokines and neuroendocrine peptides such as neuropeptide Y, peptide YY, ghrelin, and leptin, which act directly on the gut-microbiota-brain axis. Thus, exercise may serve as a rebalancing agent of the gut-microbiota-brain axis under the stimulus of chronic low-grade inflammation induced by obesity. So far, there is little evidence of modification of the gut-brain axis as a whole, and this narrative review aims to address the molecular pathways through which exercise may act in the context of disorders of the gut-brain axis due to obesity.